BRCA1 Gene Expression is Down Regulated in Both Familial and Sporadic Breast Cancer Cases in Baghdad- Iraq - Ali, Chemia Adil; Lafta, Fadhel M.; Al Sayyid, Maha Mhammed; Al-Rekabi, Abdul-Ameer N. Ghaloub (Iraqi Journal of Science, 2020)
Breast cancer is the commonest cancer and the leading cause of malignancies-related mortality in women worldwide. Understanding the underlying biology of the disease could improve patients’ stratification and may offer novel therapeutic targets and strategies. This study was set to investigate the association between BRCA1 gene expression and some of the clinical features of breast cancer patients in Baghdad-Iraq. Eighty peripheral blood samples were collected from sixty patients diagnosed with breast cancer and twenty healthy age-matched controls for BRCA1 qPCR gene expression analysis. The results showed a significant reduction in BRCA1 gene expression in all of the breast cancer patients with the vast majority of them (75%) having BRCA1expression below 25%. The down regulation of BRCA1 expression also showed consistency in breast cancer patients of both sporadic (n=45) and family history (n=15) cases,with expression averages of 18% and 20.19%, respectively. Moreover, the redcuation in BRCA1 expression was negatively associated with the disease’s grades,asbreast cancer patients with the advanced stage III (n=19) showed the lowest expression average of BRCA1 (13.8%) as compared to those in stages II (n=29) and I (n=12) of the disease (17.7% and 19.8%, respectively). Overall, the study highlights the key role of BRCA1gene expression in the development of breast cancer and suggests its potential utility in the diagnosis strategies and preventing the progression of the disease, especially the sporadic type.